PENGARUH MODEL LEARNING CYCLE 8E BERBANTUAN APLIKASI PHYSICS AT SCHOOL TERHADAP PENGUASAAN KONSEP PADA MATERI MOMENTUM DAN IMPULS KELAS X SMA - Wika Junilita; Muhammad Syafi'i; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
This research utilized the Physics At School application to utilize the Learning Cycle 8E model to explain students' conceptual mastery in class X SMA and identify any disparities in conceptual mastery for students in class X SMA. This kind of research uses a quantitative Nonequivalent Post-Test Control Group Design research design and a Quasi-Experimental research method. This research was performed at SMA Negeri 1 Teluk Kuantan using a concept mastery test on the material from Momentum and Impulse. The experimental class, which implements the Learning Cycle 8E model with assistance from the Physics At School program, is one of the two classes used in this research. In contrast, the second class uses conventional learning techniques as a control class. The data used in this research were concept mastery scores obtained from students who had learned physics using the Learning Cycle 8E model with assistance from the Physics At School program. Furthermore, the SPSS version 25 application for inferential analysis was used to examine the improvement in conceptual mastery. Based on a descriptive and inferential examination of the data, it was determined that the experimental class students' level of concept mastery increased by 73.08 points, while the control class was 69.70. In light of this, it can be said that the Learning Cycle 8E model, which is supported by the Physics At School application, has an impact on how well SMA Negeri 1 Teluk Kuantan children understand certain concepts.Key Words: Model Learning cycle 8E, Application Physics at school, Concept Mastery